Identification of patients with embolic stroke of undetermined source and low risk of new incident atrial fibrillation: The AF-ESUS score. Issue 1 (January 2021) - Ntaios, George; Perlepe, Kalliopi; Lambrou, Dimitris; Sirimarco, Gaia; Strambo, Davide; Eskandari, Ashraf; Karagkiozi, Efstathia; Vemmou, Anastasia; Korompoki, Eleni; Manios, Efstathios; Makaritsis, Konstantinos; Vemmos, Konstantinos; et al.
Background and aims: Only a minority of patients with Embolic Stroke of Undetermined Source (ESUS) receive prolonged cardiac monitoring despite current recommendations. The identification of ESUS patients who have low probability of new diagnosis of atrial fibrillation (AF) could potentially support a strategy of more individualized allocation of available resources and hence, increase their diagnostic yield. We aimed to develop a tool that can identify ESUS patients who have low probability of new incident AF. Methods: We performed multivariate stepwise regression in a pooled dataset of consecutive ESUS patients from three prospective stroke registries to identify predictors of new incident AF. The coefficient of each independent covariate of the fitted multivariable model was used to generate an integer-based point scoring system. Results: Among 839 patients (43.1% women, median age 67.0 years) followed-up for a median of 24.3 months (2999 patient-years), 125 (14.9%) had new incident AF. The proposed score assigns 3 points for age ≥ 60 years; 2 points for hypertension; −1 point for left ventricular hypertrophy reported at echocardiography; 2 points for left atrial diameter >40 mm; −3 points for left ventricular ejection fraction <35%; 1 point for the presence of any supraventricular extrasystole recorded during all available 12-lead standard electrocardiograms performed during hospitalization for the ESUS; −2 points for subcortical infarct; −3 points for the presence of non-stenotic carotid plaques. The rate of new incident AF during follow-up was 1.97% among the 42.3% of the cohort who had a score of ≤0, compared to 26.9% in patients with > 0 (relative risk: 13.7, 95%CI: 5.9--31.5). The area under the curve of the score was 84.8% (95%CI: 79.9--86.9%). The sensitivity and negative predictive value of a score of ≤0 for new incident AF during follow-up were 94.9% (95%CI: 89.3--98.1%) and 98.0% (95%CI: 95.8--99.3%), respectively. Conclusions: The proposed AF-ESUS score has high sensitivity and high negative predictive value to identify ESUS patients who have low probability of new incident AF. Patients with a score of 1 or more may be better candidates for prolonged automated cardiac monitoring. Clinical trial registration: URL:https://www.clinicaltrials.gov / Unique identifier: NCT02766205.